2022
DOI: 10.1186/s12887-022-03625-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of human adenoviruses in children with and without respiratory symptoms: Preliminary findings from a case-control study

Abstract: Background Human adenovirus (HAdV) is an important viral agent in children which can lead to severe acute respiratory infection (SARI). Reports on molecular epidemiology of HAdVs in Iran are limited. This case-control study is conducted to compare the HAdV infection rate and molecular epidemiology among two groups of children with and without respiratory symptoms in Tehran, Iran during 2018–2019. Methods Nested PCR was performed on 120 oropharyngea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…These authors therefore concluded that qualitative PCR testing for adenovirus DNA alone was not useful in the pediatric population as a diagnostic test. Zadheidar et al (2022) found similar rates of adenovirus positivity in both symptomatic children and healthy controls, but found different subtypes predominated in each Pediatric co-infection probability relative to expected based on overall infection rate. The probability of viral co-infection was calculated based on the overall incidence of each co-infection pair, and compared to the expected probability of each co-infection type based on the incidence of each virus category as would be expected from stochastic interactions (random chance).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…These authors therefore concluded that qualitative PCR testing for adenovirus DNA alone was not useful in the pediatric population as a diagnostic test. Zadheidar et al (2022) found similar rates of adenovirus positivity in both symptomatic children and healthy controls, but found different subtypes predominated in each Pediatric co-infection probability relative to expected based on overall infection rate. The probability of viral co-infection was calculated based on the overall incidence of each co-infection pair, and compared to the expected probability of each co-infection type based on the incidence of each virus category as would be expected from stochastic interactions (random chance).…”
Section: Discussionmentioning
confidence: 63%
“…population (Zadheidar et al, 2022). The increased rates of coinfection involving adenovirus seen here may therefore be partially attributable to asymptomatic colonization.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Using hemi-nested PCR assay ( 4 ) ( Table 1 ) the spanning region of partial hexon was selected for detection and genotyping of HAdV. To run the assay 5 μl of DNA extraction product, 12.5 μl Ampliqon 2× master mix, and 12.5 pmol of each primer in a total volume of 25 μl was used in the first round.…”
Section: Methodsmentioning
confidence: 99%
“…These viruses are commonly circulating in the general population which include human rhinovirus (HRV), human adenovirus (HAdV), influenza virus, respiratory syncytial virus (RSV), human metapneumovirus (hMPV), parainfluenza viruses, enterovirus, bocavirus, and coronaviruses. Of particular interest are HRV and HAdV, which can frequently result in acute respiratory tract infections (ARTI) in young children requiring hospitalizations ( 2 4 ). HRVs (family Picornaviridae , genus Enterovirus ) are nonenveloped viruses, with single-stranded RNA (ssRNA), which are classified into three species (A, B, C) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%